'I can't sit here and cry with you, I have to play'. Strategies by very young children in refugee collective accommodation. Issue 1 (2nd January 2020) - Wihstutz, Anne
ABSTRACT: Little is known about the everyday life of very young children in refugee collective accommodation centres, hosted together with their parents. Access to high-quality provision of early education and care is not implemented. Against this background, the paper explores young children's everyday life practices in these specific centres. This paper presents findings from an explorative ethnographic research project in refugee accommodation centres in Germany. Researchers accompanied 12 children aged three to seven years old in their daily play and family activities through participant observation in different refugee centres. Against the constraints of their life circumstances, refugee children's activities are discussed as children's unique ways of appropriation, demonstrating social actor-ship. In outlook, the paper highlights co-operative work with refugee parents and the use of ethnographic research findings to inform programmes in Early Childhood Education and Care.